2017
DOI: 10.1097/md.0000000000007041
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride glucose-body mass index is effective in identifying nonalcoholic fatty liver disease in nonobese subjects

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an increasingly common condition that is highly correlated with obesity; however, it is not uncommon among nonobese individuals. Triglyceride (TG) and glucose index combined with body mass index (TyG-BMI) has been proposed as a favorable marker of insulin resistance. We sought to investigate the effectiveness of TyG-BMI in identifying NAFLD in nonobese subjects.We conducted a cross-sectional study in a nonobese (BMI <25.0 kg/m2) Chinese population (N = 6809) of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 33 publications
1
49
0
2
Order By: Relevance
“…Additionally, a study by Zeng et al revealed that TyG-BMI performed better than TyG in identifying prehypertension in the non-obese population [ 14 ]. Zhang et al [ 15 ] analysed the relationship between TyG-BMI and non-obese NAFLD in a cross-sectional study. They concluded that TyG-BMI was more effective than TyG alone in identifying non-obese NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study by Zeng et al revealed that TyG-BMI performed better than TyG in identifying prehypertension in the non-obese population [ 14 ]. Zhang et al [ 15 ] analysed the relationship between TyG-BMI and non-obese NAFLD in a cross-sectional study. They concluded that TyG-BMI was more effective than TyG alone in identifying non-obese NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of all the parameters determining IR have been fully verified [ 14 ]. A cross-sectional study showed that TyG-BMI is linked to NAFLD [ 15 ]. However, it is not known whether the progression of time affects the association between TyG-BMI and NAFLD, and a subgroup analysis of gender has not been conducted, but previous studies have shown that gender affects the relationship [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, TyG Index has been validated as a reliable tool for insulin resistance assessment 25,[38][39][40] and as a biomarker to identify NAFLD. 41,42 For mice, this is the first time TyG Index is correlated with NAFLD progression, though it has already been applied for peripheral insulin resistance assessment. [43][44][45][46] We have not measured serum insulin levels for additional HOMA-IR calculation, even though it is well-documented that MSG obese mice develop hyperinsulinemia since early ages because of increased vagotonia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that triglyceride (TG)-BMI, which combines TG and blood glucose indexes with BMI, is an effective marker to detect NAFLD in nonobese patients [ 35 ]. However, the index for identifying elevated liver enzymes in PCOS women remains unknown.…”
Section: Discussionmentioning
confidence: 99%